Impact of closure of the in-house psychiatric care unit on prehospital and emergency ward length of stay and disposition locations in patients who attempted suicide: A retrospective before-and-after cohort study at a community hospital in Japan. Issue 22 (4th June 2021) - Ono, Yuko; Ono, Nozomi; Kakamu, Takeyasu; Ishida, Tokiya; Inoue, Shigeaki; Kotani, Joji; Shinohara, Kazuaki
Abstract : Abstract: Suicide is an increasingly serious public health care concern worldwide. The impact of decreased in-house psychiatric resources on emergency care for suicidal patients has not been thoroughly examined. We evaluated the effects of closing an in-hospital psychiatric ward on the prehospital and emergency ward length of stay (LOS) and disposition location in patients who attempted suicide. This was a retrospective before-and-after study at a community emergency department (ED) in Japan. On March 31, 2014, the hospital closed its 50 psychiatric ward beds and outpatient consultation days were decreased from 5 to 2 days per week. Electronic health record data of suicidal patients who were brought to the ED were collected for 5 years before the decrease in in-hospital psychiatric services (April 1, 2009–March 31, 2014) and 5 years after the decrease (April 1, 2014–March 31, 2019). One-to-one propensity score matching was performed to compare prehospital and emergency ward LOS, and discharge location between the 2 groups. Of the 1083 eligible patients, 449 (41.5%) were brought to the ED after the closure of the psychiatric ward. Patients with older age, burns, and higher comorbidity index values, and those requiring endotracheal intubation, surgery, and emergency ward admission, were more likely to receive ED care after the psychiatric ward closure. In the propensity matched analysis with 418 pairs, the after-closure group showed a significant increase in median prehospital LOS (44.0 minutes vs 51.0 minutes, P  < .001) and emergency ward LOS (3.0 days vs 4.0 days, P  = .014) compared with the before-closure group. The rate of direct home return was significantly lower in the after-closure group compared with the before-closure group (87.1% vs 81.6%, odds ratio: 0.66; 95% confidence interval: 0.45–0.96). The prehospital and emergency ward LOS for patients who attempted suicide in the study site increased significantly after a decrease in hospital-based mental health services. Conversely, there was significant reduction in direct home discharge after the decrease in in-house psychiatric care. These results have important implications for future policy to address the increasing care needs of patients who attempt suicide. Abstract : Supplemental Digital Content is available in the text